LOCAL ROOTS, GLOBAL BRANCHES: ELEMENT OF SECONDARY HISTORY EDUCATION IN THE UNITED STATES - Charles Sullivan (Universitas Negeri Yogyakarta, 2017)
The history of American education is a history of local control. Symbolized by the image of the one-room “little red schoolhouse”, from our nation’s beginnings, schools have been under the direction of local communities. Teachers were hired by local school boards, who paid their salaries and often provided housing and food as well. Curriculum was also set locally, although often through the choice of textbooks, or primers, that were the published work of various education “experts” from other places. Importantly, teachers were also fired locally. As a result, American education has long been quite sensitively calibrated to local outlooks, concerns and politics.